Paediatric gingival extra-axial chordoma: an extremely rare entity. Issue 12 (December 2022) - Winterboer, J.; Sander, B.; Korn, P.; Jehn, P.; Spalthoff, S.
Abstract: Extra-axial chordomas are rare malignant tumours. As a subcategory of axial chordomas, these tumours arise outside the axial skeleton. This report describes the case of a 13-year-old male patient with a gingival mass in the left upper jaw, who was referred to Hannover Medical School with a preliminary diagnosis of a calcifying epithelial odontogenic tumour (CEOT). Pathological examination of the enucleated tumour led to the final diagnosis of a chordoma. Thereafter, a stepwise radical resection was performed with the aim of complete resection of the tumour with wide safety margins. The main tumour mass was found to be located on the maxillary gingiva, with focal infiltration into the maxillary bone. Following resection, reconstruction was performed with a free latissimus dorsi flap. Follow-up after 1 year revealed no signs of recurrence or metastasis. This case highlights that although extremely rare, extra-axial chordoma may occur at sites distant from the midline and as such must be included in the differential diagnosis of bone and soft tissue tumours in the maxillofacial region.